APPLICATION OF OVASCAN AND PROGESTERONE CONCENTRATION FOR PREDICTION OF OVULATION DURING ESTRUS IN THE MARE - M‎., Fathalla,; L. , Yonis,; N. , Jawad, (The Iraqi Journal of Veterinary Medicine, 1987)
The estrous cycle of 8 Arabian mares was followed for one year, by visual observation of the estrous behaviour and by teasing with a stallion. Serum progesterone concentration was determined by RIA, Vaginal electric resistence was studied with aid of Ovascan, comapared with the changes in the reproductive tract as determined by rectal examination for prediction of ovulation. The changes in the reproductive tract and the behavioural manifestations expressed during the cycle indicated that the experimental mares were exhibiting estrous year arround, however, 75% of the cycles were observed during the months from March to August and 25% during the. rest of the year. The total number of cycles exhibited by the mares averaged 68 cycles, of these 22 cycles were observed during Summer, 20 during Spring, decreased to 13 cycles during Fall and 13 during Winter. the length of the estrous cycle ranged between 24-26. 31 days, the average estrus length ranged between 5.5-8.6 days andthe luteal phase ranged from 19.04-24.87 days. The ovascan readings showed decline by 50 degrees, constantly, a day preceeding ovulation, compared to the readings during the rest of estrus days and this finding was confirmed by rectal palpation of the reproductive tract in succeeding day which disclosed the disappearance of the mature follicle and the: presence of the ovulation site on the ovary, consequently, the estrous signs faded away gradually within 24-48 hours of the ovuletion. Serum progesterone concentration, during’ the estrus and one day before ovulation ranged between 0.58 -1.05 ng/ml, while mean luteal phase concentration was 10.2820.89 ng/ml. The results of the present study disclosed that the mares in Iraq could be bred any time of the year and it is most probable that measurement of progesterone concentration will have more practical application for monitring ovarian activity and estrus prediction, if. a rapid system of measurment made avilable (as progesterone strip). The application of Ovascan proved effecient tool for prediction of ovulation in the mare, providing information for synchroniztion of service with ovulation, a mean augmenting fertility and avoiding rectal palpation which hinder service.